Solutions to limit credit rish at Vietinbank-Ba Dinh branch - Lê, Diệu My (2020)
The purpose of the overall study is to assess credit quality at Vietnam Joint Stock Commercial Bank for Industry and Trade. To clarify the objective of the overall study of the topic, the author focuses on clarifying the following specificresearch objectives: Researching on the rationale related to credit risk and credit risk management activities in commercial banks; Analyzing, commenting and evaluating the status of credit risk management and credit risk management activities at Vietinbank Ba Dinh branch; Researching international experience and practices on credit risk management and improving credit risk management quality in commercial banks; From the research results found, the author proposes some solutions to improve the quality of credit risk management at Vietinbank Ba Dinh branch